In vitro activity of SecA inhibitors in combination with carbapenems against carbapenem-hydrolysing class D β-lactamase-producing Acinetobacter baumannii. (19th August 2016) - Chiu, Chun-Hsiang; Liu, Yu-Han; Wang, Yung-Chih; Lee, Yi-Tzu; Kuo, Shu-Chen; Chen, Te-Li; Lin, Jung-Chung; Wang, Fu-Der
Abstract : Objectives: According to our previous study, OXA-58 translocates to the periplasm via the Sec pathway in carbapenem-resistant Acinetobacter baumannii (CRAb). In the present study, carbapenem-hydrolysing class D β-lactamases (CHDLs) belonging to the OXA-23, OXA-40 and OXA-51 families were examined to determine whether they are also Sec-dependent. Additionally, the effects of SecA inhibitors combined with carbapenems against CHDL-producing CRAb were examined. Methods: Cell fractionation and western blot analyses were performed to detect periplasmic His-tagged CHDLs. A chequerboard analysis with pairwise combinations of carbapenems (imipenem or meropenem) and SecA inhibitors (rose bengal, sodium azide or erythrosin B) was performed using six clinical CRAb isolates harbouring different CHDL genes. The fractional inhibitory concentration (FIC) index was determined. The combination with the lowest FIC index was subjected to a time–kill analysis to examine synergistic effects. Results: In an in silico analysis, the CHDLs OXA-23, OXA-40 and OXA-51 were preferentially translocated via the Sec system. The SecA inhibitor rose bengal decreased periplasmic translocation of His-tagged OXA-23 and OXA-83 (belonging to the OXA-51 family), but not OXA-72 (belonging to the OXA-40 family) from ATCC 15151 transformants. Imipenem or meropenem with rose bengal showed synergistic effects (FIC index, ≤0.5) for six and four clinical isolates, respectively. Imipenem or meropenem with sodium azide showed no interactions (FIC index, 0.5–4) against all clinical isolates. Imipenem and rose bengal had the lowest FIC index and showed synergy at 24 h in the time–kill assay. Conclusions: Combinations of SecA inhibitors and carbapenems have synergistic effects against CHDL-producing CRAb.